Diagnostic Accuracy of Detective Flow Imaging Endoscopic Ultrasonography for Evaluating Blood Flow Within Mural Nodules of Intraductal Papillary Mucinous Neoplasms - Kazuki Endo; Haruo Miwa; Kazuya Sugimori; Kozue Shibasaki; Shoichiro Yonei; Yugo Ishino; Shotaro Tsunoda; Hayato Yoshimura; Akihiro Funaoka; Hiromi Tsuchiya; Ritsuko Oishi; Yuichi Suzuki; et al. (Diagnostics)
Background/Objectives: Detective flow imaging (DFI) endoscopic ultrasonography (EUS) can identify the microvascular flow imaging of a mural nodule (MN) in an intraductal papillary mucinous neoplasm (IPMN) without the use of contrast agents. This retrospective study evaluated the diagnostic accuracy of DFI-EUS and its ability to evaluate the blood flow of MNs in IPMNs. Methods: Between April 2021 and September 2023, 68 patients with MNs in IPMNs observed on EUS images were retrospectively analyzed. Both DFI-EUS and contrast-enhanced EUS (CE-EUS) were performed during the same session. Three expert endosonographers blinded to the patients’ clinical data assessed the MN images obtained with CE-EUS and DFI-EUS. First, DFI-EUS images were evaluated using a predefined scoring system; thereafter, CE-EUS images were evaluated. The diagnostic capability of DFI-EUS to detect MN blood flow was assessed with CE-EUS as the gold standard. Secondary outcomes included inter-reader agreement, the correlation between MN size and detection rates, and the association between DFI blood flow signal patterns and malignancy of MNs in surgically resected cases. Results: CE-EUS showed a contrast effect in the MN in 24 cases. Among these, DFI-EUS detected blood flow signals in 20 cases; false-positive results were not observed. DFI-EUS demonstrated a sensitivity of 83%, specificity of 100%, and accuracy of 93% for detecting MN blood flow. Inter-reader agreement was substantial (kappa values, 0.6–0.8). The subgroup analysis revealed that all MNs ≥ 10 mm had detectable blood flow on DFI-EUS, whereas MNs < 10 mm had reduced detection rates (75%; 12/16 cases). No significant correlation between the DFI blood flow signal patterns and MN malignancy of resected cases was observed. Conclusions: DFI-EUS demonstrated high diagnostic accuracy for detecting MN blood flow. Because of its simplicity and cost-effectiveness, DFI-EUS could be an alternative to CE-EUS for patients with MNs inside IPMNs.